ANALISIS PENURUNAN KADAR AIR GAPLEK MENGGUNAKAN ALAT PENGERING KABINET BERBASIS BIOMASSA TEMPURUNG KELAPA - Peri Ridwan Nurhedi; Juandi Muhammad (Komunikasi Fisika Indonesia, 2023)
Gaplek is one of the processed cassava products by cutting it into pieces, soaking, and drying it. The drying process for making cassava is necessary because the water content in cassava determines the quality of processed cassava products, one of which is cassava flour. The drying method that can use to dry cassava is to use a cabinet dryer based on coconut shell biomass. In this research, cassava drying was carried out using a cabinet drying machine based on coconut shell biomass. The YL-69 sensor is added to measure moisture content automatically, and then the data read will be calibrated using data from measurements using the MD7822 Grain Moisture Meter sensor. The method used for this research is the experimental method. The coconut shell biomass used was 2500 grams, and the cassava sample used was 500 grams on each drying rack. This study's results indicate a very strong correlation between measuring moisture content using the YL-69 sensor and the Grain Moisture Meter MD7822, which can be seen from the average correlation value of 0.954601. In addition, there was a significant reduction in cassava mass after drying by 44.2%, which indicated that drying with this method could dry cassava optimally.